The Influence Of Transactional Leadership, Job Skills, And Career Development On Employee Work Performance At The Central Statistics Agency Of Lahat Regency - Rara Veronica; Titi Hasanah; Marko Ilpiyanto (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the influence of transactional leadership, work skills, and career development on employee performance at the Lahat Regency Central Statistics Agency. The variables in this study were transactional leadership (X1), work skills (X2), career development (X3), and work performance (Y). The data analysis methods used were instrument testing (reliability testing, validity testing), classical assumption testing (normality testing, heteroscedasticity testing, multicollinearity testing), multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination testing. The results of the study showed that (1) transactional leadership had a significant partial effect on work performance, as evidenced by the calculated t value > t-table (2.440 > 2.040). (2) work skills had a significant partial effect on work performance, as evidenced by the calculated t value > t-table (2.177 > 2.040). (3) Career Development has a significant partial effect on Job Performance, as evidenced by the calculated t-value > t-table (3.176 > 2.040). (4) Transactional Leadership, Job Skills, and Career Development have a significant simultaneous effect on Job Performance, as evidenced by the calculated f-value > f-table (7.809> 4.160), with a significance value lower than the (a) level of 0.05 (0.000 < 0.05).